A smart nanofibre sensor based on anthocyanin/poly‐l‐lactic acid for mutton freshness monitoring. (29th June 2020) - Sun, Wuliang; Liu, Yilin; Jia, Lu; Saldaña, Marleny D. A.; Dong, Tungalag; Jin, Ye; Sun, Wenxiu
Summary: Food poisoning is a major issue worldwide. However, methods for identifying contaminants in foods are inefficient. Here, a solid dye was designed for mutton freshness monitoring by incorporating blueberry‐derived anthocyanins and degradable poly‐l‐lactic acid (PLLA). The solid dye was easily processed into ink, soft transparent film and nanofibre film. The nanofibre film prepared by electrostatic spinning (sensor) showed good colour stability at 4–25 °C. As the ammonia concentration increased, the sensor colour changed from pink to light pink and then to colourless. The detection limit was 37 ppm. The sensor could be repeatedly used. Applying the sensor to the detection of mutton freshness, it was found that the sensor colour change was directly related to the quality of mutton. The sensor could effectively monitor mutton freshness in real time and the colour changes were easily distinguished by naked eyes, suggesting its potential in intelligent packaging for freshness monitoring of meat foods. Abstract : The solid dye was easily processed into ink, soft transparent film and nanofibre film. The nanofibre sensor showed high sensitivity and colour responsiveness to ammonia. The detection limit of nanofibre sensor was 37 ppm. The nanofibre sensor could be repeatedly used. The nanofibre sensor could effectively monitor mutton freshness in real time. Colour changes of the nanofibre sensor were easily distinguished by naked eyes.